The Impact Analysis of Features and Perceived Quality on Consumer Satisfaction of Samsung Mobile Phones in Makassar City - Muliansyah, Dadah; Cahyono, Yoyok; Siagian, Ade Onny (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine whether Features and Perceived quality affect Samsung Mobile Consumer satisfaction in Makassar City. The population in this study are consumers who use Samsung mobile phones in Makassar City. Based on the research results, the regression equation is obtained as follows Y = 5.308 +0.389 X1 + 0.321 X2. Based on statistical data analysis, each indicator in this study is valid and the variables are reliable. In testing the classical assumptions, the regression model is multicolonierity free, heteroscedasticity does not occur, and is normally distributed. The results of hypothesis testing, namely the T test results prove that all independent variables, namely Features and Perceived Quality, have a positive effect on Consumer satisfaction on Samsung Mobile Phones in Makassar City and the F test shows that features and perceived quality simultaneously have a significant effect on Consumer satisfaction, with a calculated F value of 13.976 with a significance of 0.000 <0.05. The coefficient of determination R square is 0.536. This means that 53.6% of consumer satisfaction is influenced by the features and perceived quality variables, the remaining 45.3% is influenced by other variables. The coefficient of determination for R square is 0.536. This means that 53.6% of consumer satisfaction is influenced by the features and perceived quality variables, the remaining 45.3% is influenced by other variables. The coefficient of determination for R square is 0.536. This means that 53.6% of consumer satisfaction is influenced by the features variable and perceived quality, the remaining 45.3% is influenced by other variables.